Weak ferromagnetism linked to the high-temperature spiral phase of YBaCuFeO_{5} - J. Lyu; M. Morin; T. Shang; M. T. Fernández-Díaz; M. Medarde (Physical Review Research, 2022)
The layered perovskite YBaCuFeO_{5} is a rare example of a cycloidal spiral magnet whose ordering temperature T_{spiral} can be tuned far beyond room temperature by adjusting the degree of Cu^{2+}/Fe^{3+} chemical disorder in the structure. This unusual property qualifies this material as one of the most promising spin-driven multiferroic candidates. However, very little is known about the response of the spiral to magnetic fields, crucial for magnetoelectric cross-control applications. Using bulk magnetization and neutron powder diffraction measurements under magnetic fields up to 9 T, we report here a temperature-magnetic field phase diagram of this material. Besides revealing a strong stability of the spiral state, our data uncover the presence of weak ferromagnetism coexisting with the spiral modulation. Since ferromagnets can be easily manipulated with magnetic fields, this observation opens new perspectives for the control of the spiral orientation, directly linked to the polarization direction, as well as for a possible future use of this material in technological applications.